Technical safety -- an attribute of quality : an interdisciplinary approach and guideline /: an interdisciplinary approach and guideline. (2018) - Keller, H. B (Hubert B.); Pilz, Wolf-Dieter; Schulz-Forberg, Bernd; Langenbach, Christian
No abstract available